Cultural historical activity theory, double stimulation, and conflicts of motives in education science: Where have we been? (2012-2021) - Isaac, Guillaume; Barma, Sylvie; Romero, Margarida (Revue internationale du CRIRES / CRI_SAS international Journal)

(untitled) (Centre de recherche et d’intervention sur la réussite scolaire, 2021)
Cultural Historical Activity Theory (CHAT) can be used both as a theoretical and an analytical framework. It has been used in a wide variety of contexts over a wide variety of research objects in education and other fields requiring a comprehensive understanding of interactions within a system. At a theoretical level, the relation between double stimulation and instrumental mediation has been studied and understood, yet the link between double stimulation and conflicts of motives is understudied. How has scientific literature considered this avenue for research over the past ten years? A systematic literature review was conducted, and thematic analysis was performed in order to identify themes. As of the first quarter of 2021, scientific literature in education sciences does not yet reflect the interest and potential of this research avenue. Double stimulation and its relation to conflicts of motives are key components to form volitional action in education contexts and is therefore a valuable research object.